Analysing hydrological impacts of controlled drainage, peat thickness and groundwater fluxes in cultivated peat soils - Mika Tähtikarhu; Timo A. Räsänen; Jari Hyväluoma; Arndt Piayda; M. Myllys (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science)
This study analysed the effects of controlled drainage, peat layer thickness and hydrological connections on the hydrology of agricultural peatlands. A hydrological model was combined with a comprehensive field-scale dataset, consisting of several field plots with controlled and regular subsurface drainage, and with varying peat thickness. Controlled drainage markedly reduced the amount of drain discharge (up to 862 mm) during the 1.5-year simulation period, while the consequent increase in groundwater levels was modest (mean difference 0.01–0.17 and 0.10–0.21 m in thin and thick peat, respectively). Thus, controlled drainage can change flow routes, and the impact on the groundwater table can depend on the related groundwater out- and influxes. Controlled subsurface drainage had a higher potential to increase groundwater levels in areas with thick peat soils and steep upslope than in areas with a shallow peat layer and steep downslope areas. If the soils are drained efficiently during the spring, controlled drainage cannot increase groundwater levels during the following growing season if the amount of evapotranspiration exceeds the amount of precipitation and influxes. The model application complemented the knowledge gained from the empirical data. Furthermore, our analysis shows knowledge gaps regarding the hydrology of agricultural peatlands.